New Characteristics in the Changing Psychological Contracts and Repatriation Success of Expatriates in Japanese Multi-National Corporations (Global Journal of Management and Business Research, 2014)
Introduction-With more and more multi-national corporations in this globalization age, the research on effective expatriate utilization is attracting increasing attention. Because of the culture difference, the characteristics of expatriate in different countries have distinguishing charac-teristics. In this study, based on multi-dimension analysis of organization, individual, culture and institution, with cases from interview with expatriates, the new factors that influence expatriate repatriation success in Japanese multi-national corporations will be discussed..
Keywords: psychological contracts; expatriate; repatriation success; culture; institution